2021
DOI: 10.18203/issn.2455-4529.intjresdermatol20210013
|View full text |Cite
|
Sign up to set email alerts
|

Management of androgenetic alopecia: a review

Abstract: <p class="abstract">Androgenetic alopecia is a patterned hair loss disorder affecting approximately 73% of men and 57% of women in their lifetime, this affection can cause psychological effects like low self-stem and depression diminishing the quality of life. Currently, finasteride and minoxidil are the only two drugs approved by the food and drug administration (FDA), and devices of low-level laser therapy are FDA cleared. Alternative therapies for androgenetic alopecia treatment include a drug like du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The effectiveness of finasteride in countering male pattern baldness is also worth noting. 6 Finasteride stands as another medication greenlit by the US FDA for managing male pattern baldness. Studies have indicated that finasteride proficiently obstructs the enzyme responsible for converting testosterone into dihydrotestosterone, a factor known for advancing male pattern baldness.…”
Section: Exploring Minoxidil-a Game-changer In Hair Fall Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The effectiveness of finasteride in countering male pattern baldness is also worth noting. 6 Finasteride stands as another medication greenlit by the US FDA for managing male pattern baldness. Studies have indicated that finasteride proficiently obstructs the enzyme responsible for converting testosterone into dihydrotestosterone, a factor known for advancing male pattern baldness.…”
Section: Exploring Minoxidil-a Game-changer In Hair Fall Treatmentmentioning
confidence: 99%
“…5 Moreover, the topical application of minoxidil has gained approval from the US FDA for both men and women, rendering it a viable treatment avenue for androgenic hair loss. 2,6,7 In addition to minoxidil, another medication sanctioned by the US FDA for addressing androgenic hair loss in men is finasteride. 7 The emotional and social ramifications of hair loss are frequently underestimated, as the medical dimensions of the underlying conditions are generally perceived as less severe.…”
Section: Introductionmentioning
confidence: 99%